2017
DOI: 10.1021/acs.orglett.7b02092
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Pillararene Chemistry: Synthesis and Application of a 10 + 1 Functionalized Pillar[5]arene

Abstract: A novel functionality was introduced in the pillararene family by the Claisen rearrangement of monoallyl pillar[5]arene. This new key derivative can lead to the formation of a 10 + 1 functionalized derivative, a useful scaffold for further derivatization. Except for the previously known monodeprotection reaction, all steps proceed efficiently with high yields and easy separation. In addition, a solvent-responsive pseudo[1]rotaxane was synthesized based on this novel functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…A pillar[5]arene derivative has been reported that provides an interesting example of self‐inclusion complexation in the solid state, with the structure breaking when dissolved in a solvent of small molecular size but remaining intact in a larger‐molecular‐size solvent . Similarly, a pillar[5]arene‐based pseudo[1]rotaxane that forms a self‐inclusion complex in the solid state shows solvent‐responsive self‐inclusion in solution . Other examples of self‐inclusion include cyclodextrins, which exhibit self‐inclusion properties when the inclusion of bulky end groups leads to the formation of pseudo[1]rotaxane, cucurbiturils with a pendant residue acting as hydrophobic guest, and monosubstituted resorcinarenes and covalently linked dimeric resorcinarene capsules displaying intramolecular self‐inclusion properties in solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pillar[5]arene derivative has been reported that provides an interesting example of self‐inclusion complexation in the solid state, with the structure breaking when dissolved in a solvent of small molecular size but remaining intact in a larger‐molecular‐size solvent . Similarly, a pillar[5]arene‐based pseudo[1]rotaxane that forms a self‐inclusion complex in the solid state shows solvent‐responsive self‐inclusion in solution . Other examples of self‐inclusion include cyclodextrins, which exhibit self‐inclusion properties when the inclusion of bulky end groups leads to the formation of pseudo[1]rotaxane, cucurbiturils with a pendant residue acting as hydrophobic guest, and monosubstituted resorcinarenes and covalently linked dimeric resorcinarene capsules displaying intramolecular self‐inclusion properties in solution.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In supramolecular chemistry,macrocyclic hosts are important building blocks providing cavities for inclusion complexation thereby enabling the self-assembly of multiple supramolecular architectures. These supramoleculara ssemblies range from simple 1:1i nclusion complexes and pseudorotaxanes [4,5] to polymers [6][7][8][9] and particles [10,11] featuring in some cases gelation properties. [12] In particular,s upramolecular polymers are attracting increasing interest due to their uniquep roperties of self-healing, [13] stimuli-responsiveness [14] and shape memory.…”
Section: Introductionmentioning
confidence: 99%
“…Along with common decorations 35 as, for example, in per-and monofunctionalized, (A1/A2)-disubstituted, or rim-differentiated P [5]s, several newly reported P [5] substitution patterns, namely 10+1 phenylene-substituted, 36 meso-decorated, 37 and tri-/tetra-substituted 38 P [5]s are shown in in Figure 3. [5]arene functionalization patterns reported in the literature.…”
Section: Synthesizing C 5 -Symmetric Pillar[5]arenes Against the Oddsmentioning
confidence: 99%
“…As shown in Scheme , the modification of PA­[ n ]­s includes three positions: on phenyl hydroxyl groups (R 1 ), on aromatic rings A–E, or on methylene bridges (R 2 ). Predominately, phenyl hydroxyl groups are modified due to the facile synthesis. , On the contrary, there are only scattered reports on the substitution on aromatic protons or methylene bridges. Substitution on these two positions is often based on the modification of PA­[ n ]­s. The lack of chemoselectivity results in the difficulty to the control substitution number or their exact positions.…”
mentioning
confidence: 99%